To the selection of shock absorber elements of the artificial foot - G. N. Burov; L. M. Smirnova; V. A. Bolshakov; V. M. Yankovsky; O. L. Belyanin (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2023)
Introduction. Walking on a prosthesis of the lower limb is accompanied by a shock load on the artificial foot, which provokes discomfort when using the product and pain in the stump, increases the risk of trauma to the skin and the formation of arthrosis of the joints of the lower limb. These negative consequences can be reduced by the use of prosthetic modules with shock-absorbing properties. Usually, the artificial foot plays the role of a shock absorber in the prosthesis.Aim – substantiation of the choice of material for the shock-absorbing module of the artificial foot.Materials and methods. Bench tests of leaf springs made of steel, carbon and titanium alloy of different thicknesses were carried out by registering changes in their geometric characteristics under a dosed load, as well as full-scale tests of experimental artificial feet with such springs used as a load absorber. The functionality of the feet was determined by the subjective assessment of the comfort of the prosthesis by the patient and the result of the analysis of pressure dynamics under the feet. Results. The results of bench tests showed that leaf springs made of steel 2 mm thick, titanium alloy 3 mm and carbon fiber (carbon) 5.7 mm are unsuitable for use as a shock absorber in the foot of the prosthesis in terms of deflection in the longitudinal and transverse directions under load, in contrast to springs made of 3 mm steel and 4 mm titanium alloy. Field tests of experimental feet with shock-absorbing modules made of steel 3 mm thick and titanium alloy 4 mm showed their suitability for use as part of a prosthesis, which was confirmed by a positive assessment of their comfort by patients, as well as an increase in the symmetry coefficient of the duration of the roll over the artificial and intact feet when walking with experimental foot design compared to industrially manufactured.Discussion. The 4mm titanium alloy leaf spring outperforms the 3mm steel spring in terms of buckling under load, but biomechanical studies have not shown a clear preference for the experimental foot with one of these materials over the other. At the same time, each of them turned out to be more functional than the commercially manufactured foot chosen for the study. But the high corrosion resistance and low specific gravity of the titanium alloy, higher mechanical strength per unit mass compared to steel, give advantages to this material for the manufacture of shock-absorbing modules in atypical prostheses. The choice of the thickness of the elastic element can and should be calculated taking into account the weight of the disabled person.Conclusion. The manufacture of elastic elements from titanium alloys is promising when used in artificial feet for atypical prostheses that require high corrosion resistance and mechanical strength with a small mass of the product. A positive factor in the use of titanium alloys for the manufacture of foot shock absorbers in the form of leaf springs is the simplicity and low cost of the design.